MMP2 as an independent prognostic stratifier in oral cavity cancers. (1st January 2020) - Hoffmann, Caroline; Vacher, Sophie; Sirven, Philémon; Lecerf, Charlotte; Massenet, Lucile; Moreira, Aurélie; Surun, Aurore; Schnitzler, Anne; Klijanienko, Jerzy; Mariani, Odette; Jeannot, Emmanuelle; Badois, Nathalie; et al.
ABSTRACT: Background: Around 25% of oral cavity squamous cell carcinoma (OCSCC) are not controlled by the standard of care, but there is currently no validated biomarker to identify those patients. Our objective was to determine a robust biomarker for severe OCSCC, using a biology-driven strategy. Patients and methods: Tumor and juxtatumor secretome were analyzed in a prospective discovery cohort of 37 OCSCC treated by primary surgery. Independent biomarker validation was performed by RTqPCR in a retrospective cohort of 145 patients with similar clinical features. An 18-gene signature (18 G) predictive of the response to PD-1 blockade was evaluated in the same cohort. Results: Among 29 deregulated molecules identified in a secretome analysis, including chemokines, cytokines, growth factors, and molecules related to tumor growth and tissue remodeling, only soluble MMP2 was a prognostic biomarker. In our validation cohort, high levels of MMP2 and CD276, and low levels of CXCL10 and STAT1 mRNA were associated with poor prognosis in univariate analysis (Kaplan-Meier). MMP2 ( p = .001) and extra-nodal extension (ENE) ( p = .006) were independent biomarkers of disease-specific survival (DSS) in multivariate analysis and defined prognostic groups with 5-year DSS ranging from 36% ( MMP2 highENE+) to 88% ( MMP2 lowENE-). The expression of 18 G was similar in the different prognostic groups, suggesting comparable responsiveness to anti-PD-1. Conclusion: High levels of MMP2 were an independent and validated prognostic biomarker, surpassing other molecules of a large panel of the tumor and immune-related processes, which may be used to select poor prognosis patients for intensified neoadjuvant or adjuvant regimens.